Effect of Clomiphene Citrate on Fertility Hormones in Women with Polycystic Ovarian Syndrome - Arshad, Asma; Rehman, Kashif Ur; Butt, Hamama Islam; Bashir, Shahzad; Umar, Fatima; Yaseen, Zahida; Zahra, Kashish; Bakhsh, Ahmad (International Health Review, 2024)
This study aims to investigate the positive effect of Clomiphene Citrate (CC) in inducing ovulation in women with PCOS. Clomiphene Citrate is a non-steroidal drug that primarily affects estrogen production. CC also has pronounced effects on balancing of the female hormones, normal ovulation process, and overcoming the PCOS-based infertility issues. Hormonal profile evaluation including follicle stimulating hormone (FSH), luteinizing hormone (LH), progesterone, and estrogen was performed at Clinical Laboratory, Services Hospital, Lahore. Serum volume of the aforementioned hormones were determined in PCOS-suffering infertile women (n=50) and healthy fertile women (n=50) by using a commercially available ELISA kit manufactured by Calbotech lnc. Serum luteinizing hormone (LH), follicle stimulating hormone (FSH), progesterone, and estrogen mean values in PCOS patients before the use of CC were evaluated as 5.74±0.939 (IU/L), 3.804±1.163 (IU/L), 2.098±1.233 (ng/ml), and (51.458±7.091 pg/ml respectively, while after management with CC the mean value of serum LH, FSH, Progesterone, and Estrogen were 3.716±0.513 (IU/L), 5.644±1.130 (IU/L), 10.704±2.313 ng/ml and 37.72±4.969 pg/ml respectively, which indicated a significant differences in hormonal pattern . The current study demonstrates that Clomiphene Citrate (CC) has positive effects in ovulation process in females with polycystic ovarian syndrome (PCOS), within the local population.